A novel bacterial protease inhibitor adjuvant in RBD-based COVID-19 vaccine formulations containing alum increases neutralizing antibodies, specific germinal center B cells and confers protection against SARS-CoV-2 infection in mice - Coria, Lorena M. (2022)
In this work, we evaluated recombinant receptor binding domain (RBD)-based vaccine formulation prototypes with potential for further clinical development. We assessed different formulations containing RBD plus alum, AddaS03, AddaVax, or the combination of alum and U-Omp19: a novel Brucella spp. protease inhibitor vaccine adjuvant. Results show that the vaccine formulation composed of U-Omp19 and alum as adjuvants has a better performance: it significantly increased mucosal and systemic neutralizing antibodies in comparison to antigen plus alum, AddaVax, or AddaS03. Antibodies induced with the formulation containing U-Omp19 and alum not only increased their neutralization capacity against the ancestral virus but also cross-neutralized alpha, lambda, and gamma variants with similar potency. Furthermore, the addition of U-Omp19 to alum vaccine formulation increased the frequency of RBD-specific geminal center B cells and plasmablasts. Additionally, U-Omp19+alum formulation induced RBD-specific Th1 and CD8+ T-cell responses in spleens and lungs. Finally, this vaccine formulation conferred protection against an intranasal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) challenge of K18-hACE2 mice.